Chronic Critical Illness Patients Fail to Respond to Current Evidence‐Based Intensive Care Nutrition Secondarily to Persistent Inflammation, Immunosuppression, and Catabolic Syndrome. Issue 7 (6th February 2020) - Rosenthal, Martin D.; Bala, Trina; Wang, Zhongkai; Loftus, Tyler; Moore, Frederick
Abstract: Background: Sepsis‐induced multiple‐organ failure (MOF) has plagued surgical intensive care units (ICUs) for decades. Early nutrition (principally enteral) improves hospital outcomes of high‐risk ICU patients. The purpose of this study is to document how the growing epidemic of chronic critical illness (CCI) patients responds to adequate evidence‐based ICU nutrition. Methods: This retrospective post hoc subgroup analysis of an ongoing sepsis database identified 56 CCI patients who received early, adequate nutrition per an established surgical ICU protocol compared with 112 matched rapid‐recovery (RAP) patients. Results: The matched CCI and RAP groups had similar baseline characteristics. Serial biomarkers showed that CCI patients remained persistently inflamed with ongoing stress metabolism and that despite receiving evidence‐based protocol nutrition, they had persistent catabolism and immunosuppression with more secondary infections. More CCI patients were discharged to poor nonhome destinations (ie, skilled nursing facilities, long‐term acute care, hospice) (81% vs 29%, P < 0.05). At 12‐month follow‐up, CCI patients had worse functional status by Zubrod score (3.17 vs 1.62, P < 0.001) and Short Physical Battery Testing (4.78 vs 8.59, P < 0.02), worse health‐related quality of life by EQ‐5D‐3L descriptive measures (9.07 vs 7.45, P < 0.003), and lower survival (67% vs 92%, P < 0.05). Conclusions: Despite early, adequate, evidence‐based ICU nutrition, septic surgical ICU patients who develop CCI exhibit persistent inflammation, immunosuppression, and catabolism with unacceptable long‐term morbidity and mortality. Although current evidence‐based ICU nutrition may improve short‐term ICU outcomes, novel adjuncts are needed to improve long‐term outcomes for CCI patients.